Application of Doctor-Nurse-Patient Integration Management Mode in Patients with Endometriosis - Yao CHEN; Zhihuai MO; Jianyong CAO; Zhaojuan SU; Yuexia ZHANG; Fang CHEN; Jianying WANG (Tehran University of Medical Sciences, 2018)
Background: To investigate the effect of applying doctor-nurse-patient integration management mode to patients with endometriosis (EMT). Methods: A total of 160 patients with EMT from the Department of Neurology of The Fifth Affiliated Hospital Sun Yat-Sen University from January 2017 to October 2017 were selected. They were divided into control group and experimental group according to the time sequence of hospitalization, with 80 patients in each group. The traditional nursing management mode was implemented in the control group, and doctor-nurse-patient integration mode was implemented in the experimental group. The psychological status, quality of life, and satisfaction of the 2 groups of patients were compared one year after surgery. Results: The anxiety and depression scores in the observation group were (41.89±7.50) and (42.40±7.40) points, respectively, and those in the control group were (57.55±9.68) and (55.00±9.35) points, respectively. The differences between the two groups were statistically significant (t=-11.44, -9.42, P<0.05). The improvement rate of quality of life (sleep, work and sexual life) in the observation group was 87.5%, which was higher than that in the control group (63.8%). The difference between the 2 groups was statistically significant (U=583, P<0.01). The satisfaction rate in the observation group was 90.00%, which was higher than that in the control group (78.75%) (U=592.00, P< 0.01). Conclusion: The doctor-nurse-patient integration management mode can effectively improve the negative psychological status and quality of life of patients with EMT and improve patient satisfaction, which is worth popularizing.